The Influence of Audit Knowledge and Experience on the Detection of Regional Loss Findings - Mahaputra, M. Rizky; Mahaputra, M. Ridho (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
This study aims to obtain information and analyze the effect of audit knowledge and experience on the detection of regional loss findings. This research was conducted at the Regional Inspectorate of Sijunjung Regency. The sampling method used the personally administered questionnaires technique. The test used is multiple regression. The results of the study show that audit knowledge and experience have an effect on the detection of regional loss findings. Based on the results of multiple linear regression tests, it was found that the most dominant variable was audit knowledge.